Multimodalitas Transportasi Non-Motorized Kawasan Halte BRT Kota Yogyakarta - Widianto, Refli; Rakhmatulloh, Anita Ratnasari (Jurusan Perencanaan Wilayah dan Kota, 2024)
In order to maintain sustainability, the transportation system must consider environmental factors. Lack of public interest is a problem for the implementation of BRT as an effort to transition to sustainable transportation. In an effort to increase the variety of services, it is crucial to have access to transportation options, notably non-motorized, low-pollution vehicles. Descriptive and buffered analysis utilizing GIS is therefore used in this study to identify the characteristics of multimodal non-motorized transportation. The study's findings highlight the dearth of transportation options around bus stops, particularly when considering the effectiveness of non-motorized transportation. The majority of multimodal connection has uniform or homogenous properties.